Specific Adsorption of Tumor‐Affinity Proteins to Improve Tumor Accumulation for Targeted Imaging and Therapy - Xiaoyao Xiong; Sijia Li; Yumin Li; Kangzheng Wang; Suying Xu; Chang Guo; Leyu Wang (Small, 2026)
ABSTRACT Nonspecific protein adsorption on nanocarriers leads to the formation of a protein corona, which promotes macrophage phagocytosis and attenuates delivery efficacy. We report a new surface engineering strategy to functionalize nanoplatforms by introducing trifluoroethyl sulfoxide, which not only effectively inhibits the adsorption of macrophage‐friendly proteins (ascribed to the hydrophilic sulfoxide group) but also promotes the specific adsorption of tumor‐affinity proteins (attributed to the trifluoroethyl group), thereby efficiently suppressing macrophage phagocytosis and increasing tumor accumulation. The results of the control nanoplatforms with different surfaces show that simply increasing surface anti‐protein adsorption ability does not significantly improve tumor accumulation, although it can prolong the blood circulation. By co‐loading immunomodulator NLG919 and AuPt nanocrystals (chemodynamic agent), the nanoplatforms demonstrate excellent specific adsorption capacity of tumor‐affinity proteins including transferrin and fibronectin. Cellular and animal experiment results show that this nanoplatform presents excellent tumor uptake and therapeutic capabilities. Moreover, the intrinsic fluorine atoms serve as built‐in probes for background‐free 19 F MRI, enabling non‐invasive and real‐time monitoring of nanoplatform biodistribution. This work provides a brand‐new idea for the design of nanotheranostics with good anti‐macrophage phagocytosis capacity and excellent tumor accumulation ability for imaging‐guided therapy.